Young People's Voices Regarding the Use of Social Networking Sites to Plan for a Night Out Where Alcohol Is Involved. Issue 3 (3rd July 2021) - Hutton, Alison; Rubin, Mark; Sloand, Elizabeth; Goodwin Veenema, Tener; Prichard, Ivanka; Gray, Katherine L.; Harper, Soleil
ABSTRACT: The risk of alcohol related harm is experienced disproportionality by young people aged 15–24 years. Harmful use of alcohol has serious effects on individual physical and mental wellbeing and is considered by the World Health Organization to be one of the main risk factors for poor health globally. It is crucial to understand the factors that influence drinking behavior in young people in order to inform prevention strategies to prevent problematic drinking. This is particularly paramount during the transition into young adulthood (around 18–25 years), when risky health behaviors are likely to become embedded. This pilot study adopted a qualitative descriptive methodology that facilitates exploration of what young people say about their own experiences and behavior, as it relates to SNS use and alcohol consumption. Semi-structured interviews were conducted in Newcastle, NSW Australia. An inductive, semantic approach to thematic analysis was selected to analyze the data as this method supported the exploratory nature of the pilot study and ensured that the themes identified were strongly linked to the data. Four main organizing themes that arose from the collected data were: organizing friends; safety amongst friends, planning not to plan; and different event – different plans. All of the participants stated they preferred to use Facebook Messenger™ to connect and share in a group conversation with peers. Convenience, cost and accessibility emerged as the main reasons for using SNSs to plan nights out. Planning for a night out using SNSs allows young people to impulsively plan and change plans – making planning fluid and asynchronous. To date, despite the global use of SNSs, the influence of SNSs in young adults' planning for events during which alcohol is served is relatively unknown. This pilot study gives us a some understanding of how young people use SNSs to plan and prepare for a night out where alcohol is served. Further research needs to be conducted to determine whether SNSs can be used effectively to promote health behavior change or be used as forums for advice seeking and support when attending events where alcohol is served, with the ultimate goal of lowering risky behaviors and thereby improving health outcomes for young people.